Efficacy and safety of prebiotics, probiotics, and synbiotics on hemoglobin and anemia in the pediatric population: A systematic review and meta-analysis - Gladys Estheysi Elías Solís; Steffi Aleksandra Maraza Pacori; Salomon Huancahuire-Vega; David R. Soriano-Moreno (PLoS ONE, 2026)
Aim To evaluate the efficacy and safety of prebiotics, probiotics, and synbiotics on hemoglobin levels and anemia in the pediatric population. Methods We conducted a systematic review and meta-analysis of randomized clinical trials (RCTs). PubMed, Embase, and CENTRAL were searched up to August 2025. We included RCTs assessing prebiotics, probiotics, or synbiotics on hemoglobin or anemia in children. Random-effects meta-analyses were performed, and certainty of evidence was assessed using GRADE and minimal important differences. The protocol was registered in PROSPERO (CRD420251108276). Results Nineteen RCTs involving 4188 children were included. Compared to placebo or standard care, prebiotics, probiotics, and synbiotics (alone or with iron) showed no important effects on hemoglobin, hematocrit, or ferritin (certainty: high to very low). However, probiotics versus placebo may reduce anemia (1 RCT; RD: -−6 per 100; 95% CI: -−15 to +6, low certainty). No serious adverse events were reported; observed events were mainly mild gastrointestinal symptoms. Conclusion Prebiotics, probiotics, and synbiotics do not provide clinically important benefits on hemoglobin or anemia in children, although they appear safe. Larger, high-quality trials in high-risk populations are needed.